2019
DOI: 10.1101/557900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA adenosine methylase (MTA) deposits m6A on pri-miRNAs to modulate miRNA biogenesis in Arabidopsis thaliana

Abstract: m 6 A, one of the most abundant mRNA modifications, has been associated with various metabolic processes in plants. Here we show that m 6 A also plays a role in miRNA biogenesis in Arabidopsis thaliana. Significant reductions in plant m 6 A/MTA levels results in lower accumulation of miRNAs whereas pri-miRNA levels tend to be higher in such plants. m 6 A-IP Seq and MTA-GFP RIP were used to show that many pri-miRNAs are m 6 A methylated and are bound by MTA, further demonstrating that pri-miRNAs can also be sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…It is a question of outstanding importance to define if and how the labeling of these many housekeeping transcripts by m 6 A contributes to plant growth and development. Finally, a recent report deposited in bioRxiv shows that primary microRNA transcripts in Arabidopsis also contain m 6 A and proposes that the modification regulates microRNA biogenesis (Bhat et al, 2019), as previously proposed in animals (Alarcón et al, 2015;Berulava et al, 2015).…”
Section: Occurrence Of M 6 a In Plant Transcriptomesmentioning
confidence: 59%
“…It is a question of outstanding importance to define if and how the labeling of these many housekeeping transcripts by m 6 A contributes to plant growth and development. Finally, a recent report deposited in bioRxiv shows that primary microRNA transcripts in Arabidopsis also contain m 6 A and proposes that the modification regulates microRNA biogenesis (Bhat et al, 2019), as previously proposed in animals (Alarcón et al, 2015;Berulava et al, 2015).…”
Section: Occurrence Of M 6 a In Plant Transcriptomesmentioning
confidence: 59%
“…More than 150 RNA modifications have been identified as post-transcriptional regulatory markers in a variety of RNA species, including messenger RNA (mRNA), transfer RNA (tRNA), ribosomal RNA (rRNA), small non-coding RNA (snRNA), and long non-coding RNA (lncRNA), RNA methylation is one of the post-transcriptional modifications of RNA, and N 6 -methyladenosine (m 6 A) is the most common type of RNA methylation modification, accounting for more than 80% of RNA methylation modifications in organism. Current study suggests that the m 6 A modification plays an important role in RNA fate, such as RNA splicing (Liu et al, 2015(Liu et al, , 2017Haussmann et al, 2016;Lence et al, 2016;Xiao et al, 2016;Pendleton et al, 2017), RNA stability (Wang et al, 2014;Du et al, 2016;Mishima and Tomari, 2016;Huang et al, 2018), RNA export (Roundtree et al, 2017;Edens et al, 2019), 3 untranslated region (UTR) processing (Ke et al, 2015;Bartosovic et al, 2017;Wei et al, 2018;Yue et al, 2018), translation (Zhou et al, 2015;Choi et al, 2016;Li et al, 2017;Shi et al, 2017), and miRNA processing (Alarcón et al, 2015a,b;Bhat et al, 2019). Although the presence of m 6 A was detected in mammals (Desrosiers et al, 1974;Wei et al, 1975;Schibler et al, 1977) and plants (Kennedy and Lane, 1979;Nichols, 1979) in the 1970s, it had not received much attention because it was considered to be "static" due to the method of detecting m 6 A sites.…”
Section: Introductionmentioning
confidence: 99%
“…Second, several regulatory proteins affecting miRNA transcription (e.g., CDC5, NOT2, and ELP2) have been shown to interact with processing machinery proteins (Wang et al, 2013; Zhang et al, 2013; Fang et al, 2015a). Notably, a recent study showed that mRNA adenosine methylase (MTA), a homologous protein of animal METTL3, deposits m 6 A onto pri-miRNAs and may impact miRNA biogenesis via its dual interaction with Pol II and Tough (TGH), a known miRNA processing regulator (Ren et al, 2012b; Bhat et al, 2019). Another intriguing finding is that many proteins affecting MIRNA gene transcription, pri-miRNA stability, and/or processing have reported or proposed functions in RNA splicing (Yu et al, 2017b).…”
Section: Other Regulatory Proteins Influencing Mirna Biogenesismentioning
confidence: 99%